Analysing the Indonesian Governance’s Performance on Climate Change Issues - Muhammad, Muhammad; Al-Atas, Mohammad Ilham; Kholifah, Umi (Jurnal Administrasi Publik, 2024)
Climate change throughout Earth's history has continued to change in a slow process of time. Today, however, these changes are increasing faster than in previous years. Governments, in this case, the Indonesian government certainly must do anything necessary to take care environmental problems.  Moreover, geographically, the territory of Indonesia is included in the area that is vulnerable to the effects of climate change. In addition, developing countries including Indonesia are considered to have higher vulnerability due to various non-physical aspects. This study will use a qualitative approach with relevant research sources, which will focus on the extent to which the Indonesian governance actors (government, private sector, and civil society) are trying to address climate change and see the dynamic between those actors. This paper highlights the failures of each actor on the efforts in addressing climate change and environmental problems. This paper finally suggests that in the end, civil society hold pivotal role to control the environmental performance of the other two actors.